The Myth of the Texas Miracle in Education - Haney, Walt (Education Policy Analysis Archives, 2000)
I summarize the recent history of education reform and statewide testing in Texas, which led to introduction of the Texas Assessment of Academic Skills (TAAS) in 1990-91. A variety of evidence in the late 1990s led a number of observers to conclude that the state of Texas had made near miraculous progress in reducing dropouts and increasing achievement. The passing scores on TAAS tests were arbitrary and discriminatory. Analyses comparing TAAS reading, writing and math scores with one another and with relevant high school grades raise doubts about the reliability and validity of TAAS scores. I discuss problems of missing students and other mirages in Texas enrollment statistics that profoundly affect both reported dropout statistics and test scores. Only 50% of minority students in Texas have been progressing from grade 9 to high school graduation since the initiation of the TAAS testing program. Since about 1982, the rates at which Black and Hispanic students are required to repeat grade 9 have climbed steadily, such that by the late 1990s, nearly 30% of Black and Hispanic students were "failing" grade 9. Cumulative rates of grade retention in Texas are almost twice as high for Black and Hispanic students as for White students. Some portion of the gains in grade 10 TAAS pass rates are illusory. The numbers of students taking the grade 10 tests who were classified as "in special education" and hence not counted in schools' accountability ratings nearly doubled between 1994 and 1998. A substantial portion of the apparent increases in TAAS pass rates in the 1990s are due to such exclusions. In the opinion of educators in Texas, schools are devoting a huge amount of time and energy preparing students specifically for TAAS, and emphasis on TAAS is hurting more than helping teaching and learning in Texas schools, particularly with at-risk students, and TAAS contributes to retention in grade and dropping out. Five different sources of evidence about rates of high school completion in Texas are compared and contrasted. The review of GED statistics indicated that there was a sharp upturn in numbers of young people taking the GED tests in Texas in the mid-1990s to avoid TAAS. A convergence of evidence indicates that during the 1990s, slightly less than 70% of students in Texas actually graduated from high school. Between 1994 and 1997, TAAS results showed a 20% increase in the percentage of students passing all three exit level TAAS tests (reading, writing and math), but TASP (a college readiness test) results showed a sharp decrease (from 65.2% to 43.3%) in the percentage of students passing all three parts (reading, math, and writing). As measured by performance on the SAT, the academic learning of secondary school students in Texas has not improved since the early 1990s, compared with SAT takers nationally. SAT-Math scores have deteriorated relative to students nationally. The gains on NAEP for Texas fail to confirm the dramatic gains apparent on TAAS. The gains on TAAS and the unbelievable decreases in dropouts during the 1990s are more illusory than real. The Texas "miracle" is more hat than cattle.